Implementasi Pengelolaan Kelas dalam Menciptakan Lingkungan Belajar yang Kondusif Di SDIT Al-Fatih - Shofwa Nursiniah; Rusi Rusmiati Aliyyah; Irwan Efendi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Classroom management plays a crucial role in fostering a comfortable and effective learning atmosphere, thereby supporting the success of the learning process. This study aims to examine the implementation of classroom management in creating a conducive learning environment at SDIT Al-Fatih, while also identifying the resulting impacts and various challenges encountered during instruction. A qualitative approach with a case study design was employed. Research informants comprising the school principal and teachers were selected using a purposive sampling technique. Data were collected through non-participant observation, semi-structured interviews, and document analysis. Data analysis utilized an interactive model involving data condensation, data display, and conclusion drawing and verification. Data validity was tested through technique triangulation. The results indicate that classroom management at SDIT Al-Fatih has been effectively implemented through the maintenance of clean, tidy, and comfortable classrooms; adequate lighting and ventilation; flexible furniture arrangements; consistent classroom discipline; and the integration of Islamic values ​​into instruction. This implementation has positively impacted students' comfort, concentration, motivation, and self-confidence, as well as the smooth flow of the learning process. However, certain challenges remain, such as limited infrastructure, unequal distribution of learning facilities, and seating arrangements that do not fully accommodate students' needs. Consequently, continuous evaluation and development of classroom management practices are necessary to create a higher-quality learning environment.